(untitled) (Journal of the College of Basic Education, 2022)
The Man of Property (1906 ) , the first book of John Galsworthy’s first trilogy , The Forsyte Saga , is intended to be a criticism of the possessive instinct in the modern social life . The research aims at the evils of that instinct , that holds modern man’s interests and attention , how destructive the effect of property has been upon the Forsyte family , most represented by Soames Forsyte , who are characterized by their desire to increase their wealth , self preservation , lack of imagination and their disbelief in love , beauty , and philosophical ideas . It sheds light on this family’s reversed concept of property , their acquisitive attitudes and their suffocating moral codes , that bring about their final degradation . The core of John Galsworthy’s criticism in The Man of Property was the English upper – middle class family , known as the Forsyte family that survived from 1886 to the advent of the nineteen- twenties . Through The Man of Property ,Galsworthy tried to show the decline and degeneration of the bourgeois family , how their manners and behaviour changed " as the Victorian era came to an end and the 20th century began . " 1 As an Edwardian , Galsworthy in his works challenged the ideals of society often depicted in the 19th century literature . He examined the destructive force of private property and its impact on human behaviour , how this force or instinct opposed the idea of beauty , love and imagination , " which the Forsytes do not take into their philosophy " 2 and which " upset their plans and disturb their emotional life . " 3 This very idea is carefully explained by Galsworthy himself in his preface through which he intends to clarify the title of the novel , that he " used with a suitable irony . " 4 In this view and using Galsworthy’s words , the main theme of the novel is " the impingement of beauty and the claims of freedom on a possessive world " 5 , how beauty has become a source of disturbance in the lives of men .This theme is best exemplified in the story of Irene Forsyte , the wife of the novel’s central character and it is the one